Quantifying Coloring Skills Among Preschoolers. - Huang, Chien-Yu; Lin, Gong-Hong; Lu, Szu-Ching; Lee, Shih-Chieh (American Journal of Occupational Therapy)
Importance: Coloring is popular with preschool children and reveals their developmental state. However, interpreting coloring performances is challenging because descriptive and subjective evaluations are commonly used with large variations. Objective: To develop a scoring method to objectively quantify children's coloring skills. Design: Colored blank train templates were analyzed using four indicators (entropy, complexity, coloring outside the lines, and unexpected blank areas) to form a summed score. Setting: Kindergarten in a urban city (Tainan, Taiwan). Participants: Two hundred thirty-nine typically developing children ages 3 to 6 yr. Outcome and Measures: A newly developed method to assess coloring skill on the basis of a colored picture of a train. Results: The summed score exhibited good internal consistency (Cronbach's α =.80), discriminative validity (p =.04), convergent validity (rs =.66 and.59 with age and visual–motor integration), and acceptable factorial validity (comparative fit index =.99, standardized root-mean-square residual =.04, and root-mean-square error of approximation =.13). Moreover, three coloring patterns (mature, transitional, and immature) were identified. Conclusions and Relevance: The new method provides objective, reliable, and valid scores representing coloring skills in typically developing children. In addition, the coloring patterns can be recognized. This method can be used to facilitate comparisons of children's coloring skills with peers and provide valuable insight into children's development. Plain-Language Summary: This study proposes a new method to objectively quantify children's coloring skills with sound reliability and validity in typically developing children. The method can be used to evaluate children's coloring skills and patterns to shed light on their developmental stages. This study proposes a method to facilitate comparisons of children's coloring skills with peers that can provide valuable insights into children's development.